Influence of pulping process conditions towards better water resistant effect of durian shell paper by lignin: Two level factorial design approach - Arif @ Harip, Afraha Baiti; Munawar, Rose Farahiyan; Abdul Rashid, Muhammad Faiz Haiqal; Abd Razak, Jeefferie; Mohd Abid, Mohd Asyadi 'Azam; Abd Manaf, Mohd Edeerozey; Ismail, Syahriza; Dimin @ Mohd Amin, Mohd Fairuz; Abdullah, Hazwani Husna (Asian Research Publishing Network (ARPN), 2017)
Chemical pulping of durian shell fiber is a comparatively new approach in the field of pulping, and the paper industry as a whole. Pressures of rising wood resource consumption have resulted in increased attention on the use of non-wood raw materials in the papermaking industry. This situation is due to trees being exploited in high numbers for the purpose of paper manufacturing. Thus, some alternative solutions have been developed to remedy this. Natural resources wastes like kenaf, bamboo and sugarcane bagasse are used as the raw material to produce these varied grades of paper. Additionally, cellulose fiber possesses a natural tendency to absorb moist and water vapor from the surrounding, producing weak mechanical properties and limiting paper's use. Therefore, in this study, lignin acts as a natural plasticizer in plant cell wall has been optimized to overcome the hygroscopic issue. An optimal amount of lignin will generate maximum hydrophobic effect to prepare for the production of water resistant paper. The process is optimized under the influence of three operational variables; 1) % of NaOH, 2) cooking temperature, and 3) period of cooking. To analyze the response, two level factorial design method by Design Expert v.6.0.8 software has been used. The results show that the highest water contact angle reading of 70.33° has been achieved at the condition of 17 % alkalinity, 140 °C of cooking temperature and 120 min of cooking period. At the same process condition, the highest amount of lignin (57.67 %) has also been obtained which showing the significant interaction between lignin and the hydrophobic effect. From the analysis of variance (ANOVA), all parameters have significantly affected the reading of water contact angle. The P-value of the experiment model is less than 0.0001 and the coefficient of determination value (R2) is 1.000. This conclusively suggested that the model is significant and influences on the precision and process-ability of the production.